Estradiol for the mitigation of adverse effects of androgen deprivation therapy. Issue 8 (August 2017) - Russell, Nicholas; Cheung, Ada; Grossmann, Mathis
Abstract : Prostate cancer (PCa) is the second most commonly diagnosed cancer in men. Conventional endocrine treatment for PCa leads to global sex steroid deprivation. The ensuing severe hypogonadism is associated with well-documented adverse effects. Recently, it has become apparent that many of the biological actions attributed to androgens in men are in fact not direct, but mediated by estradiol. Available evidence supports a primary role for estradiol in vasomotor stability, skeletal maturation and maintenance, and prevention of fat accumulation. Hence there has been interest in revisiting estradiol as a treatment for PCa. Potential roles for estradiol could be in lieu of conventional androgen deprivation therapy or as low-dose add-back treatment while continuing androgen deprivation therapy. These strategies may limit some of the side effects associated with conventional androgen deprivation therapy. However, although available data are reassuring, the potential for cardiovascular risk and pro-carcinogenic effects on PCa via estrogen receptor signalling must be considered.